Impact of Zn substitution on Fe(II)-induced ferrihydrite transformation pathways. (1st March 2022) - Yan, Jinshu; Frierdich, Andrew J.; Catalano, Jeffrey G.
Abstract: Iron oxide minerals are ubiquitous in soils, sediments, and aquatic systems and influence the fate and availability of trace metals. Ferrihydrite is a common iron oxide of nanoparticulate size and poor crystallinity, serving as a thermodynamically unstable precursor to more crystalline phases. While aging induces such phase transformations, these are accelerated by the presence of dissolved Fe(II). However, the impact of trace metals on Fe(II)-catalyzed ferrihydrite phase transformations at ambient temperatures and the associated effects on trace metal speciation has seen limited study. In the present work, phase transformations of ferrihydrite that contains the trace metal zinc in its structure were investigated during aging at ambient temperature in the presence of two different Fe(II) concentrations at pH 7. X-ray diffraction reveals that low Fe(II) concentration (0.2 mM) generates hematite plus minor lepidocrocite, whereas high Fe(II) concentration (1.0 mM) produces a magnetite-lepidocrocite mixture. In both cases, a substantial fraction of ferrihydrite remains after 12 days. In contrast, zinc-free ferrihydrite forms primarily lepidocrocite and goethite in the presence of 0.2 mM Fe(II), with minor hematite and a trace of ferrihydrite remaining. For 1.0 mM Fe(II), magnetite, goethite, and lepidocrocite form when zinc is absent, leaving no residual ferrihydrite. Transformations of zinc-ferrihydrite produce a transient release of zinc to solution, but this is nearly quantitatively removed into the mineral products after 1 h. Extended X-ray absorption fine structure spectroscopy suggests that zinc partitions into the newly formed phases, with a shift from tetrahedral to a mixture of tetrahedral and octahedral coordination in the 0.2 mM Fe(II) system and taking on a spinel-like local structure in the 1.0 mM Fe(II) reaction products. This work indicates that substituting elements in ferrihydrite may play a key role in promoting the formation of hematite in low temperature systems, such as soils or sediments. In addition, the retention of zinc in the products of ferrihydrite phase transformation shows that trace metal micronutrients and contaminants may not be mobilized under circumneutral conditions despite the formation of more crystalline iron oxides. Furthermore, mass balance requires that the abundance and isotopic composition of iron oxide-associated zinc, and possibly other trace metals, in the rock record may be retained during diagenetic phase transformations of ferrihydrite if catalyzed by dissolved Fe(II).